The characteristics of professional competence of engineer pedagogue with economic expertise and its structure - Lazarchuk, H. V. (Problems of Engineer-Pedagogical Education, 2018)
The essence of professional competence is defined on the basis of analysis of different scholars' definitions of it as one of the person's competence to effectively fulfill professional responsibilities. On the basis of analysis of such concepts as "engineer", "engineer pedagogue", "economist" the distinctive features of professional activity of engineer pedagogue with economic expertise are defined. The features of professional competence of engineer pedagogue that are defined by his professional responsibilities are described. On the basis of engineer pedagogues' professional competence analysis the main types of professional activity are defined. It was generalized that the professional should have professional competence to fulfill professional responsibilities effectively. The components of professional competence are competences that are needed to fulfill professional responsibilities.